Modeling and Managing Context-Aware Systems' Variability - Mens, Kim; Capilla, Rafael; Hartmann, Herman; Kropf, Thomas (IEEE software, 2017)
This theme issue provides an updated perspective on techniques to manage software system variability at runtime, to make software systems smarter and less dependent on human intervention.